Semiabelian and self-returning of points of n-ary groups - Kulazhenko, Yu.I. (Algebra and Discrete Mathematics, 2014)
In this article new criterian Semiabelian of n-ary Groups is expressed through Self-Returning free point comparatively element specially built to sequences, consisting of mediums of all sides free polygonal figure with even number of the tops and one tops this polygonal figure in term symmetrical point and vector.